High-pressure reversibility in a plastically flexible coordination polymer crystal - Xiaojiao Liu (Nature Portfolio, 2021)
Mechanically flexible single crystals are promising materials for advanced technological applications. Here, the authors study the high pressure response of a plastically flexible coordination polymer and provide indication of an overall disparate mechanical response of bulk flexibility and quasi-hydrostatic compression within the same crystal lattice.